The Comprehensive Systematic Review of Efficacy of Dietary Supplements for Headaches - Adrian Saleh (The International Journal of Medical Science and Health Research, 2026)
Introduction: Migraine and other primary headache disorders represent a significant global health burden, often inadequately managed by conventional pharmacotherapy due to issues of efficacy, side effects, and patient preference. This has spurred interest in dietary supplements as potential prophylactic and therapeutic alternatives. This report synthesizes the current evidence on the efficacy and safety of various dietary supplements for headache management. Methods: A systematic approach was employed to identify relevant studies involving participants with primary headache disorders, interventions with standalone dietary supplements, and quantitative headache-related outcomes. Data were extracted on supplement details, headache types, participant characteristics, outcomes, efficacy results, study design, and safety profiles from included studies. Results: The analysis demonstrated significant efficacy for several supplements. Omega-3 fatty acids, particularly when combined with reduced omega-6 intake (H3-L6 diet), reduced headache days by 4.0 days per month (Ramsden et al., 2021). High-dose EPA/DHA outperformed FDA-approved prophylactic medications in a network meta-analysis (Tseng et al., 2023). Vitamin B2 (400 mg/day) significantly reduced migraine frequency and showed comparable efficacy to sodium valproate with fewer side effects (Chen et al., 2021; Rahimdel et al., 2015). Magnesium (500-600 mg/day), Coenzyme Q10, vitamin D, and butterbur also showed consistent benefits. B-vitamin combinations were effective, particularly in individuals with specific MTHFR genotypes (Lea et al., 2009; Menon et al., 2012). Probiotics, curcumin, alpha-lipoic acid, and minerals like zinc and selenium also demonstrated positive effects. Combination therapies (e.g., CoQ10 + L-carnitine, omega-3 + nano-curcumin) often showed synergistic benefits. Discussion: The efficacy of supplements is moderated by factors such as dosage, formulation, genetic makeup (e.g., MTHFR status), headache chronicity, and age. Supplements appear to work through diverse mechanisms including anti-inflammation, mitochondrial support, oxidative stress reduction, and neuromodulation. They present a favorable safety profile compared to many pharmaceutical preventatives. Conclusion: A robust body of evidence supports the use of specific dietary supplements—including omega-3 fatty acids, riboflavin, magnesium, CoQ10, and vitamin D—as effective and generally safe options for the prophylaxis of migraines and other primary headaches. They offer viable alternatives or adjuncts to conventional pharmacotherapy, especially for patients seeking fewer side effects or with specific biological predispositions. Future research should focus on long-term safety, optimal dosing protocols, and personalized supplementation strategies based on biomarkers and genetics.